Imaging of Gastric Carcinoma. Part Two: Lymph node mapping in Gastric Carcinoma - Maru, Pulkit; Roy, Bipradas; Sen, Saugata; Chatterjee, Argha (Journal of Gastrointestinal and Abdominal Radiology, 2021)
Accurate preoperative nodal staging is critical in determining the appropriate therapy and prognosis for stomach cancer. A staging computed tomography should inform the treating surgeon about the nodal burden to decide the appropriate surgical plan or perioperative chemotherapy. Nodal staging is also a powerful predictor of the outcome of surgery and overall survival. Imaging of nodes is also important in the assessment of response following the chemotherapy. In this article, we will discuss lymphatic drainage of stomach and different nodal stations, identification of nodal stations on cross sectional imaging, and different types of surgical nodal clearance for gastric cancer.
Keywords: nodal staging; stomach; cancer; computed tomography